Nomads and networks the ancient art and culture of Kazakhstan - Stark, Soren; Rubinson, Karen Sydney 1943-; Samashev, Z. S. (Zainolla Samashevich); Chi, Jennifer; Alimbai, Nursan (Institute for the Study of the Ancient World, 2012)
Presents an unparalleled overview of the sophisticated culture of pastoral nomadic populations who lived on the territory of present-day Kazakhstan from roughly the middle of the first millennium BCE to the early centuries CE.--Book Jacket.